(untitled) (MAUSAM, 1970)
Considered theoretically, convective clouds formed in highly polluted air and, as such in air over-rich in its condensation nuclei content, are less liable to precipitate than similar clouds forming in normally clean air. This aspect of relative raininess of clouds formed under differing nucleus state of air has been examined by comparative study of precipitation behaviour of thunder clouds during pre-monsoon months over Calcutta, grouped under three classes as discussed in the paper.